19 An analysis of 59, 644 PCI cases in patients with previous CABG: is there a legacy effect of coronary perforation?. (27th November 2017) - Kinnaird, Tim; Anderson, Richard; Ossei-Gerning, Nicholas; Cockburn, James; Sirker, Alex; Ludman, Peter; deBelder, Mark; Johnson, Tom; Baumbach, Andreas; Copt, Samuel; Zaman, Azfar; Mamas, Mamas A
Abstract : Background: The evidence base for coronary perforation (CP) occurring during PCI in patients with a history of bypass surgery (PCI-CABG) is limited and the long-term effects unclear. Methods: Data analysed from the BCIS dataset on all PCI-CABG procedures performed between 2005 and 2013. Multivariate logistic regressions and propensity scores were used to identify predictors of CP and its association with outcomes. Results: During the study period, 309 coronary perforations were recorded during 59, 644 PCI-CABG procedures with the incidence rising from 0.32% in 2005 to 0.68% in 2013 (p<0.001 for trend). Independent associates of perforation were age (odds ratio (OR) 95% confidence intervals 1.03 [1.02–1.05], p<0.001), female gender (OR 1.74 [1.21–2.49], p=0.002), hypertension (OR 1.83 [1.25–2.69], p<0.001), chronic occlusive disease (OR1.89 [1.23–2.64], p<0.001) and rotational atherectomy use (OR 2.44 [1.42–4.17], p=0.002). In-hospital clinical complications including Q-wave MI (2.9 vs 0.2%, p<0.001), major bleeding (14.0 vs 0.9%, p<0.001), blood transfusion (3.7 vs 0.2%, p<0.001), and death (10.0 vs 1.1%, p<0.001) were more frequent in patients with coronary perforation. A legacy effect of perforation on mortality was evident, with an odds ratio for 12 month mortality of 1.35 for perforation survivors compared to matched non-perforation survivors without a CP (p<0.0001). Conclusions: Coronary perforation is an infrequent event during PCI-CABG but has a significant impact on in-hospital clinical events. A legacy effect of perforation on 12 month mortality was observed.